IDENTIFICATION OF MPT64 GENE MUTATION IN THE CLINICAL ISOLATES OF MYCOBACTERIUM TUBERCULOSIS COMPLEX (MTBC) BASED ON CORD FACTOR DETECTION - Asarina, Shinta
Mycobacterium tuberculosis complex (MTBc) infection may have a similar clinical symptom to non-tuberculosis mycobacteria (NTM) infection, but the treatments for these two diseases are very different. Recently, the incidence and prevalence of both Tuberculosis and NTM infection has increased. Thus an accurate differentiation of MTBc and NTM is needed. The MPT64 Rapid Test is one of the most widely used MTBc detection methods because it is high in sensitivity and specificity. However, several studies have reported variations in the accuracy of this test due to potential mutations in the mpt64 gene. Therefore, all MPT64 test-negative results will be considered as NTM, potentially leading to misdiagnosis and inappropriate patient treatment. In addition to MPT64 test, cord factor formation can also be used to differentiate MTBc from NTM. This study aims to identify and characterize mpt64 gene mutations in the clinical isolates of MTBc from patients with suspected MTBc infection in Bandung based on the presence of cord factor. MPT64 test (Rapid Test SD Bioline TBAgMPT64) and cord factor detection were carried out on 1424 mycobacterial isolates. Isolates with MPT64 test-negative but produce cord factor were then subjected to DNA extraction and PCR amplification using specific primer for mpt64. Isolates that yielded PCR product were subjected to full-length mpt64 gene sequencing and then analyzed using MUSCLE. The protein structure of mpt64 was predicted using Swiss Model. We found 13 isolates to be MPT64 test-negative but produce cord factor. Only 7 out of 13 isolates yielded PCR product and confirmed as MTBc. Sequence analysis of mpt64 showed several mutations which are 5-bp (1 isolate), 6-bp (1 isolate) and 63-bp deletion (5 isolates). These mutations are causing amino acid and epitope alteration of mpt64 antigen, causing them to go undetected by the MPT64 test. Our findings suggest that the presence of cord factor in MTBc isolate with a negative MPT64 test result may indicate mutation in mpt64 gene.